HSV1/2 Genital Infection in Mice Cause Reversible Delayed Gastrointestinal Transit: A Model for Enteric Myopathy - Chaudhury, Arun; Dendi, Vijaya Sena Reddy; Chaudhury, Mousumi; Jain, Astha; Kasarla, Madhukar Reddy; Panuganti, Kiran; Jain, Gaurav; Ramanujam, Abhijit; Rena, Bhavin; Koyagura, Sudheer Reddy; Fogla, Sumit; Kumar, Sunil; et al. (Frontiers in Medicine, 2018)
In an interesting investigation by Khoury-Hanold et al (2016), genital infection of mice with herpes simplex virus 1 (HSV1) were reported to cause multiple pelvic organ involvement and obstruction. A small subset of mice succumbed after the first week of HSV1 infection. The authors inferred that the mice died due to toxic megacolon. In a severe form of mechanical and/or functional obstruction involving gross dilation of the colon and profound toxemia, the presentation is called “toxic megacolon.” The representative observations by Khoury-Hanold likely do not resemble toxic megacolon. The colon was only slightly dilated and benign appearing. Importantly, HSV1 infection affected the postjunctional mechanisms of smooth muscle relaxation like the sildenafil-response proteins, which may have been responsible for defective nitrergic neurotransmission and the delayed transit. Orally administered polyethylene glycol reversed the gastrointestinal “obstruction”, suggesting a mild functional type of slowed luminal transit, resembling constipation, rather than toxic megacolon, which cannot be reversed by an osmotic laxative without perforating the gut. The authors suggest that the mice did not develop HSV1 encephalitis, the commonly known cause of mortality. The premature death of some of the mice could be related to the bladder outlet obstruction, whose backflow effects may alter renal function, electrolyte abnormalities and death. Muscle strip recordings of mechanical relaxation after electrical field stimulation of gastrointestinal, urinary bladder or cavernosal tissues shall help obtain objective quantitative evidence of whether HSV infection indeed cause pelvic multi-organ dysfunction and impairment of autonomic neurotransmission and postjunctional electromechanical relaxation mechanisms of these organs.